2010
DOI: 10.1007/s10900-010-9336-4
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening Adherence in African–American Men and Women 50 Years of Age and Older Living in Maryland

Abstract: African Americans experience disproportionate incidence and mortality rates from colorectal cancer (CRC). This health disparity is partially explained by low participation in screening. This study aimed to identify factors influencing adherence to colorectal cancer screening among African Americans. Telephone interviews were conducted with African Americans living in Maryland (57% response rate). A total of 504 respondents agreed to participate. The survey primarily assessed participation in CRC screening, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…In fact, the present result is consistent with previous studies in finding that a health professional's recommendation is an important factor contributing to the use of CRC screening (Etzioni et al, 2004;Fernandez et al, 2008;Griffith, 2009;Palmer et al, 2011). The low uptake rate of CRC screening in the study populations can be largely explained by the low rate of health professionals' recommendations for such testing, suggesting that a recommendation from a health professional is the strongest external cue to action.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, the present result is consistent with previous studies in finding that a health professional's recommendation is an important factor contributing to the use of CRC screening (Etzioni et al, 2004;Fernandez et al, 2008;Griffith, 2009;Palmer et al, 2011). The low uptake rate of CRC screening in the study populations can be largely explained by the low rate of health professionals' recommendations for such testing, suggesting that a recommendation from a health professional is the strongest external cue to action.…”
Section: Discussionsupporting
confidence: 91%
“…The low uptake rate of CRC screening in the study populations can be largely explained by the low rate of health professionals' recommendations for such testing, suggesting that a recommendation from a health professional is the strongest external cue to action. Only 7% of the GP and 3% of the EM groups in the current study population received a recommendation from a health professional, much lower figures than the 67-68% of the ethnic minority group (African-Americans) reported in studies conducted in the US (Griffith, 2009;Palmer et al, 2011). Also, previous studies have found that barriers to professional recommendation include prior patient refusal of screening, lack of reminder or test tracking systems, and a lack of knowledge of the recommended screening modalities (Sewitch et al, 2006;Guerra et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Also, some physicians' recommendations regarding specific CRC tests may be influenced by reimbursement policies and rates from insurance providers. This may in turn influence their beliefs (Guessous et al, 2010; Palmer et al, 2010 Nov 24). …”
Section: Discussionmentioning
confidence: 99%
“…Although there are multiple acceptable modalities for colorectal cancer (CRC) screening in the United States such as fecal occult blood test (FOBT) and fecal DNA testing, double contrast barium enema, CT colonography, flexible sigmoidoscopy, and colonoscopy (Levin et al, 2008), the uptake of CRC screening is suboptimal in the general population (Carcaise-Edinboro and Bradley, 2008; Palmer et al, 2011; Seeff et al, 2004; Shapiro et al, 2001; Shapiro et al, 2008). Previous studies have shown that a lack of patient awareness is a commonly reported barrier to undergoing screening, while having seen a physician within the past year, spending adequate time discussing screening, and lower perceived barriers to CRC testing are strongly associated with increased uptake of CRC screening (Bazargan et al, 2009; Carcaise-Edinboro and Bradley, 2008; Seeff et al, 2004).…”
Section: Introductionmentioning
confidence: 99%